Soluble low-Km 5'-nucleotidase from electric-ray (Torpedo marmorata) electric organ and bovine cerebral cortex is derived from the glycosyl-phosphatidylinositol-anchored ectoenzyme by phospholipase C cleavage. - Vogel, M (1992)
Soluble and membrane-bound low-Km 5'-nucleotidase was isolated from high-speed supernatants and membrane fractions derived from the electric organ of the electric ray (Torpedo marmorata) or from bovine brain cerebral cortex. Purification of both enzymes included chromatography on concanavalin A-Sepharose and AMP-Sepharose. The contribution to the total of soluble enzyme activity was lower in electric organ (1.6%) than in bovine cerebral cortex (27.9%). Membrane-bound and soluble forms have very similar Km values for AMP and are inhibited by micromolar concentrations of ATP. Both forms cross-react with, and are inhibited by, an antibody against the membrane-bound surface-located (ecto-) 5'-nucleotidase from electric organ. The HNK-1 carbohydrate epitope is present on both forms of the Torpedo enzyme, but is entirely absent from bovine cerebral-cortex 5'-nucleotidase. An antibody specific for the inositol 1,2-(cyclic)monophosphate that is formed on phospholipase C cleavage of an intact glycosyl-phosphatidylinositol (GPI) anchor binds to the soluble, but not to the membrane-bound, form of the enzyme from both sources. Our results suggest that soluble low-Km 5'-nucleotidase in both electric organ and bovine brain is derived from the membrane-bound GPI-anchored form of the enzyme by the action of a phospholipase C and is not a soluble cytoplasmic enzyme.